The Influence Of Profitability, Liquidity, Solvency, Activities, And Company Size On Company Value (Empirical Study of Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2021) - Puja indah paramitha; Erwin febriansyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to determine the effect of profitability, liquidity, solvency, activity and firm size on firm value. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange in 2019-2021. While the samples obtained were 28 companies. The technique of determining the sample using a purposive sampling technique, the research method is a quantitative method. This study uses the Package For Social Science Statistical Software (SPSS 22). The results showed that profitability had no effect on firm value with a significance value of 0.229> 0.05, solvency had no effect on firm value with a significance value of 0.0.243> 0.05, liquidity had no effect on firm value with a significance value of 0.525 > 0.05, activity has an influence on firm value with a significance value of 0.034 <0.05, and firm size has no effect on firm value with a significant value of 0.081 > 0.05, while simultaneously the independent variables affect the dependent variable with significant value 0.040 <0.05.